FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA BARU TA 2023/2024 MEMILIH PROGRAM STUDI MANAJEMEN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Tamba, Darwis; Sitanggang, Abdonsius (Jurnal Manajemen dan Bisnis, 2024)
This research aims to analyze factors affecting new students’ decisions in selecting the Management Study Program at the Faculty of Economics and Business, Universitas Katolik Santo Thomas, for the Academic Year 2023/2024. The study, involving 187 new students, employs questionnaires and interviews, with factor analysis used for data analysis. Key factors influencing decisions include accreditation status, image perception, parental influence, availability of student dormitories, fee absence, faculty members’ education level, reputation, educator friendliness, and family recommendations. The study recommends adding variables for a comprehensive understanding of factors influencing students, providing insights for improving higher education management. Future research should consider expanding the respondent pool during each admission cycle.